Human Papillomavirus‐type distribution in anogenital lesions of prepubertal children. (5th February 2021) - Braun, S.A.; Silling, S.; Schloer, S.M.; Hofmann, S.C.; Fritzen, B.; Oellig, F.; Lehmann, P.; Homey, B.; Assaf, C.; Emmert, S.; Fölster‐Holst, R.; Tigges, C.; et al.
Abstract: Background: In contrast to adults, only limited data are available on the human papillomavirus (HPV)‐type spectrum in anogenital warts (AGW) of children. Objective: This study aimed to evaluate the HPV‐type spectrum in AGW of prepubertal children. Materials & methods: In a retrospective German multicentre study, HPV genotyping was performed in AGW biopsies of 55 1‐ to 12‐year‐old children using HPV group‐specific PCRs followed by hybridization with type‐specific probes or sequence analysis. Results: Human papillomavirus‐DNA was found in 53 of the 55 AGW. In 58.5% (31/53) of the HPV‐positive AGW, mucosal HPV types were detected. HPV6 (27/53, 50.9%) was the predominant type. 43.4% (23/53) of the lesions were induced by cutaneous HPV types (HPV2, HPV27, HPV57). Mucosal HPV types were significantly more common in children under 5 years of age than in children 5 years of age and older (22/25, 88.0% [95% CI: 70.0–95.8] vs. 9/28, 32.1% [95% CI: 17.9–50.7], P  < 0.001). In contrast, cutaneous HPV types were significantly more prevalent in the 5‐ to 12‐year age group (4/25, 16.0% [95% CI 6.4–34.7] vs. 19/28, 67.9% [95% CI 49.3–82.1], P  < 0.001). Conclusion: Anogenital warts in 5‐ to 12‐year‐old children are frequently associated with cutaneous HPV types, possibly due to horizontal transmission. HPV typing, in addition to comprehensive clinical and psychosocial evaluation, can potentially help in the assessment of these cases.